La muerte de las lenguas: hacia unas consideraciones generales - Corredor Tapias, Joselyn (Universidad Pedagógica y Tecnológica de Colombia, 2014)
AbstractThis article provides some general considerations about language death . The paper first presents a definition of this interesting phenomenon, it discloses some of the ways of disappearing languages, then the article proposes information about causes of language death, later, it shows some general aspects of endangered languages extinction, and the resurrection of languages. Finally, the article concludes with some general ideas on the topicsaddressed.Key words: Sociology of language, language death, causes, to resurrect.